Cellular mechanisms of pattern formation in the developing limb - Maini, P; Solursh, M (1991)
Development of spatial pattern and form is an important, yet poorly understood phenomenon in embryology. Although genes ultimately control pattern formation, the study of the genetic aspects alone will not elucidate the mechanisms by which the developmental pathways of individual cells in a multicellular system are determined in a spatially coordinated manner. Morphogenesis of the vertebrate limb is particularly amenable to biological analysis and has been widely studied both experimentally and theoretically. It is believed that the process of limb development in mammals is similar to that in the chick, and thus, understanding the process in the chick would greatly enhance the understanding of development in other vertebrate systems. Moreover, the insights gained in understanding limb development may help in understanding the mechanisms at work in other types of pattern formation in developmental biology.